Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41433-021-01548-4
|View full text |Cite
|
Sign up to set email alerts
|

Recurring themes during cataract assessment and surgery

Abstract: The aim of this review was to discuss frequently encountered themes such as cataract surgery in presence of age-related macular degeneration (AMD), dementia, Immediate Sequential Bilateral Cataract Surgery (ISBCS), discussing non-standard intraocular lens (IOL) options during consultation in the National Health Services (NHS) and the choice of the biometric formulae based on axial length. Individual groups of authors worked independently on each topic. We found that cataract surgery does improve visual acuity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…The mean ± SD AL for all patients was 24.03 ± 2.00 mm. Taking the broadly normal range for AL as ∼22 to 26 mm, 19 25 , 27 there were no conditions in this cohort with mean AL below the lower limit of this range, but for four conditions the mean AL was above the upper limit of this range.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The mean ± SD AL for all patients was 24.03 ± 2.00 mm. Taking the broadly normal range for AL as ∼22 to 26 mm, 19 25 , 27 there were no conditions in this cohort with mean AL below the lower limit of this range, but for four conditions the mean AL was above the upper limit of this range.…”
Section: Resultsmentioning
confidence: 92%
“…The particular cut-offs were chosen as these are frequently used to define short and long eyes, particularly in clinical contexts, such as in the planning of cataract surgery and lens replacement. 19 25 …”
Section: Methodsmentioning
confidence: 99%
“…Our experience in Sheffield promoted routine listing of ISBCS in an NHS public teaching hospital in the UK and showed that in the one-year period following the reopening of cataract service from the initial COVID-19 pandemic wave, 6.1% (208/3402 eyes) of cataract operations performed were ISBCS with the vast majority of cases performed under LA (89%) in contrast to 11% under GA. A recent review by Chandra et al confirmed ISBCS is a sustainable alternative to DSBCS with comparable clinical and refractive outcomes as well as extremely low rates of bilateral endophthalmitis. 13 ISBCS has been increasingly favoured by patients demonstrated on a patient survey in NHS. 14 From patients' perspective, it helps to improve patient and family convenience and to reduce required hospital visits for preoperative and post-operative assessments.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review by Chandra et al confirmed ISBCS is a sustainable alternative to DSBCS with comparable clinical and refractive outcomes as well as extremely low rates of bilateral endophthalmitis. 13 ISBCS has been increasingly favoured by patients demonstrated on a patient survey in NHS. 14 From patients’ perspective, it helps to improve patient and family convenience and to reduce required hospital visits for pre-operative and post-operative assessments.…”
Section: Discussionmentioning
confidence: 99%